Penyelesaian Sengketa Suami Istri Melalui Mediasi dalam Perspektif Al-Qur’an dan Hadis - Annisa Fausya; Abdul Halim Talli; Zulhas’ari Mustafa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines how mediation is used to resolve marital disputes from the perspectives of the Qurâ€™an and Hadith. Qurâ€™an Surah an-NisÄâ€™ (4):35 serves as the primary basis for appointing two hakam (arbitrators) as mediators to prevent divorce, while the Prophetâ€™s ï·º Hadith provides moral guidance in the form of justice, respectful communication, and the preservation of confidentiality. Using a literature review method, this study shows that mediation in Islam not only functions to reduce conflict but also to restore relationships at a deeper level. In the context of modern households, the Islamic mediation model remains relevant as a peaceful solution before taking legal action.